EFFECT OF SERVICE QUALITY ON CUSTOMER SATISFACTION IN PT. PAWNSHOP SYARIAH TEMPE UNIT WAJO DISTRICT - Azhari, Aslan (Institute for Research and Community Service, 2019)
Customer satisfaction is the concern of PT. Pawnshop Syariah Tempe Unit Wajo District. This research was conducted with the aim of: (1) knowing the effect of physical evidence on customer satisfaction, (2) knowing the effect of reliability on customer satisfaction, (3) knowing the effect of responsiveness on customer satisfaction, (4) knowing the effect of guarantees on customer satisfaction, ( 5) knowing the effect of empathy on customer satisfaction, (6) knowing the most dominant factor influencing the dimensions of service quality on customer satisfaction at PT. Pawnshop Syariah Tempe Unit Wajo District. This study uses primary data through questionnaires totaling 100 samples from all customers of PT. Pawnshop Syariah Tempe Unit is 52,338 customers. This research was conducted in the study period from October to December 2016. The analysis method used was descriptive analysis, validity test, reliability test, classic assumption test, multiple linear regression test, partial test, simultaneous test , and the coefficient of determination test. Data were analyzed using the Statistical Product and Service Solution (SPSS) 21 software program. The results of this study indicate that: (1) physical evidence has a positive and significant effect on customer satisfaction, (2) reliability has a positive and significant effect on customer satisfaction, (3) responsiveness has a positive and significant effect on customer satisfaction, (4) guarantee has a positive effect and significant to customer satisfaction, (5) empathy has a positive and significant effect on customer satisfaction, (6) guarantee is the most influential factor on customer satisfaction at PT. Pawnshop Syariah Tempe Unit Wajo District. This means that the company management in this case PT. Pawnshop Syariah Tempe Unit needs to pay special attention to the dimensions of service quality (physical evidence, reliability, responsiveness, assurance, empathy) so that it is always used to provide good service, because it has a great influence on customer satisfaction.